Teknik Effleurage Massage terhadap Nyeri Dissmenore - Putri Andanawarih; Miftachul Jannah; Swasti Artanti (Jurnal Kebidanan Harapan Ibu Pekalongan, 2020)
Complaints of dissmenorrhea occur in 60-90% of adolescents and are the most frequent causes of absenteeism from lectures and reduced daily activities. Dissmenorrhea that is felt in the form of pain or cyclic pain along with menstruation and often feels like cramps in the stomach and can spread to the back, accompanied by nausea and vomiting. Handling of dissmenorrhea can be done by means of the effleurage technique, the effleurage technique to stimulate the stimulation of the stomach that is experiencing pain which can provide a comfortable effect. This type of research used a quasi-experimental, quasi-experimental research design, the population in this study used a random sampling technique with a total of 15. The results of the normality test of menstrual pain data before treatment were 0.33 and after treatment was 0.14 which means p> 0.05. This shows that the data is normally distributed, so the statistical test used is the Paired T-test. Based on the Paired T-test significance test, it was found that the significance value (p) is 0.00 using the provision that the degree of error (Î±) is 5% or 0.05 so that there is a difference between menstrual pain before efflurage massage and after efflurage massage. In this study, it was found that there was a decrease in the level of menstrual pain after efflurage massage compared to before efflurage massage, this proves that massage with the efflurage technique can reduce pain.